COMBINING ABILITY OF INBRED LINES DERIVED FROM A YELLOW DENT MAIZE SYNTHETIC CMS 61 - MEIRELLES, WALTER FERNANDES; GAMA, ELTO EUGENIO GOMES E; OLIVEIRA, ANTÔNIO CARLOS DE; PACHECO, CLESO ANTÔNIO PATTO; GUIMARÃES, PAULO EVARISTO DE OLIVEIRA; PARENTONI, SIDNEY NETTO; TEIXEIRA, FLÁVIA FRANÇA (International Journal of Maize & Sorghum, 2009)
A breeding program based on heterosis exploitation needs the knowledgment of the germplasm to produce good combinations in superior hybrids. A study was conducted to evaluate inbred lines, derived from synthetic maize CMS 61, in a diallel mating design. The identified lines could be possible nominees for superior yielding hybrids combinations with a flint heterotic group. Ten inbred were crossed to form 45 single crosses. Parental inbred and crosses together with a single cross commercial hybrid were evaluated using a 7 x 8 simple rectangular lattice design at four locations during the 2000/01 crop season. Ear yield (kg/ha) is discussed. For this analysis, the Griffing´s method 2, model 1 was employed. The combining ability analysis of variance showed highly significant (P< 0.01) effects for locations, crosses and lines, general combining ability (GCA), specific combining ability (SCA) and GCA x L. Genotype x Locations and SCA x Locations were also significant (P< 0.05). Means of the crosses over the four locations ranged from 6113kg/ha to 8924kg/ha. Results showed that the non-additive gene effects were more important than the additive. The selected lines should prove useful germplasm to a breeding program in tropic.